MiRNA-142-3P and FUS can be Sponged by Long Noncoding RNA DUBR to Promote Cell Proliferation in Acute Myeloid Leukemia - Yin, Zhao; Shen, HuiJuan; Gu, Chun ming; Zhang, Ming qi; Liu, Zhi; Huang, Jing; Zhu, Yangmin; Zhong, Qi; Huang, Yizhen; Wu, Feima; Ou, Ruiming; Zhang, Qing; et al. (Frontiers in Molecular Biosciences, 2021)
Acute myeloid leukemia (AML) represents a frequently occurring adulthood acute leukemia (AL). Great progresses have been achieved in the treatment of AML, but its pathogenic mechanism remains unclear. This study reported the biological functions of lncRNA DUBR in AML pathogenic mechanism. As a result, lncRNA DUBR showed high expression level within AML, resulting in poor prognosis, especially in M4 AML. In vitro studies elucidated that knockdown of DUBR with small interfering RNA (siRNA) resulted in the suppression of survival and colony formation ability, as well as induction of apoptosis, in AML cells. RNA pull-down assay and computational revealed that DUBR could sponge with miRNA-142-3P and interact with FUS protein. MiRNA-142-3P have a negative correlation with DUBR and overexpression of miRNA-142-3P inhibited cell growth in AML. Meanwhile, DUBR promoted the expression of FUS protein, targeting inhibition of FUS significantly promoted cell apoptosis in AML cell lines. In conclusion, these results revealed new mechanism of lncRNA DUBR in AML malignant behavior, and suggested that the manipulation of DUBR expression could serve as a potential strategy in AML therapy.